A study on kerf and material removal rate in wire electrical discharge machining based on Taguchi method - Tosun, N; Cogun, C; Tosun, G (Elsevier Science Sa, 2004)
This paper presents an investigation on the effect and optimization of machining parameters on the kerf (cutting width) and material removal rate (MRR) in wire electrical discharge machining (WEDM) operations. The experimental studies were conducted under varying pulse duration, open circuit voltage, wire speed and dielectric flushing pressure. The settings of machining parameters were determined by using Taguchi experimental design method. The level of importance of the machining parameters on the cutting kerf and MRR is determined by using analysis of variance (ANOVA). The optimum machining parameter combination was obtained by using the analysis of signal-to-noise (S/N) ratio. The variation of kerf and MRR with machining parameters is mathematically modeled by using regression analysis method. The optimal search for machining parameters for the objective of minimum kerf together with maximum MRR is performed by using the established mathematical models. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: WEDM; kerf; material removal rate; Taguchi method; optimization